Bactéria azospirillum brasilense e seus efeitos na eficiência da adubação nitrogenada, em cultivares convencionais de milho verde - Dias, Vanderlan Carneiro (Universidade Federal do Tocantins, 2021)
The cultivation of green corn (Zea Mays L.) is of paramount food importance and its activity is practiced by small and medium producers, generating income in family farming. The search for conservation alternatives using Azospirillum brasilense has been an alternative and cheap. The work studied conventional maize cultivars (Zea mays L.), with A. brasilense, and N rates, for green maize yield. Two experimental tests were carried out (12/04/2019 and 12/10/202) respectively, at UFT, Palmas -TO. Experimental design was randomized blocks, with three replications, in sub-divided plots, where in the plots the treatments involving seed inoculation with Azospirillum (C Az) and without (S Az). In the sub-plots the doses of N (00, 30, 60, 90 and 120 kg ha-1) and in the sub-plots eight maize cultivars. The thesis was divided into four chapters: Chapter 1 was studied the efficiency and response of corn cultivars, regarding the use of N, for the processes (C Az and S Az). Az. in seeds promoted changes in the efficiency and response of cultivars to nitrogen use. The N-efficient cultivars with Az were BM-3061, BRS-2022 and AG-1051. The BRS-3046 stood out for being efficient and responsive. Chapter 2, each process (C Az and S Az), a study of adaptability and stability (EBERHART & RUSSELL 1966) and environmental stratification (LIN, 1982), each N dose, in each trial and each process (C Az and S Az) represented a distinct environment. There was a differential response of cultivars between the processes with and without Az. The bacterium resulted in an increase in green corn yield. The BRS-3046 and AG-1051 had extensive adaptation to environments. Chapter 3, correlation coefficients (r) between traits were estimated with (PREV) for (S Az) and (C Az), at low N (30 kg ha-1 N) and at high N (120 kg ha- 1 N). There was an effect of nitrogen and Az. fertilization on the magnitude of the direct and indirect effects of the characteristics on PREV. The selection of AP in high N, with C Az and S Az, and in low N, S Az, increased PREV. At low N, without Az, the PR could be used for PREV increments. Chapter 4, each proc. (C Az and S Az), in BN and AN, carried out the study of genetic divergence between cultivars. Six characteristics were used: AP, CR, LR, PR, CED, DED, and PREV. In each proc. (S Az) and (C Az), in BN and AN, the (D2) was used as a dissimilarity measure, and the Tocher and Singh grouping was used to quantify the relative contribution of the characteristics. Az. and N doses influenced the expression of genetic variability. BM 3061, in high N, and AG 1051, in low N, were the most divergent in both inoculation processes. The PREV feature may be useful for further studies and selection of contrasting genotypes.